EEG nálezy u nemocných se systemovým lupus erythematosus - Peterová, V; Faber, J; Dostál, C; Seidl, Z; Obenberger, J; Viták, T; Danes, J; Olejárová, M (Sbornik lekarsky, 1999)
We have examined electroencephalography (EEG) and Mini-Mental State Examination (MMSE) in 38 patients with verified diagnosis of systemic lupus erythematosus (SLE). In the clinical neurological finding there were epileptic attacks in 9 patients, 10 patients suffered from stroke, 15 patients from lupus headache, 4 patients from psychosis, in 15 patients cranial neuropathy was present, in one person extrapyramidal syndrome. EEG findings were in 12 patients normal (32%), in 26 patients abnormal (66%). In 3 cases there were focal abnormalities (8%), in 19 cases episodic ones (48%), four times abnormalities were diffuse (10%). Diffuse abnormalities correlated in EEG findings with case history of GM attacks.
Keywords: dospělí; záznam o duševním stavu; Adult; elektroencefalografie; Middle Aged; lidé; systémový lupus erythematodes; Electroencephalography; Humans; Lupus Vasculitis, Central Nervous System; Male; mužské pohlaví; Mental Status Schedule; Lupus Erythematosus, Systemic; vaskulitida centrálního nervového systému při lupus erythematodes; lidé středního věku; ženské pohlaví; Female